Machine learning enables completely automatic tuning of a quantum device faster than human experts - H. Moon (Nature Portfolio, 2020)
To optimize operating conditions of large scale semiconductor quantum devices, a large parameter space has to be explored. Here, the authors report a machine learning algorithm to navigate the entire parameter space of gate-defined quantum dot devices, showing about 180 times faster than a pure random search.